Extensive Thioautotrophic Gill Endosymbiont Diversity within a Single Ctena orbiculata (Bivalvia: Lucinidae) Population and Implications for Defining Host-Symbiont Specificity and Species Recognition - Shen Jean Lim (American Society for Microbiology, 2019)
ABSTRACT Seagrass-dwelling members of the bivalve family Lucinidae harbor environmentally acquired gill endosymbionts. According to previous studies, lucinid symbionts potentially represent multiple strains from a single thioautotrophic gammaproteobacterium species. This study utilized genomic- and transcriptomic-level data to resolve symbiont taxonomic, genetic, and functional diversity from Ctena orbiculata endosymbiont populations inhabiting carbonate-rich sediment at Sugarloaf Key, FL (USA). The sediment had mixed seagrass and calcareous green alga coverage and also was colonized by at least five other lucinid species. Four coexisting, thioautotrophic endosymbiont operational taxonomic units (OTUs), likely representing four strains from two different bacterial species, were identified from C. orbiculata. Three of these OTUs also occurred at high relative abundances in the other sympatric lucinid species. Interspecies genetic differences averaged about 5% lower at both pairwise average nucleotide identity and amino acid identity than interstrain differences. Despite these genetic differences, C. orbiculata endosymbionts shared a high number of metabolic functions, including highly expressed thioautotrophy-related genes and a moderately to weakly expressed conserved one-carbon (C1) oxidation gene cluster previously undescribed in lucinid symbionts. Few symbiont- and host-related genes, including those encoding symbiotic sulfurtransferase, host respiratory functions, and host sulfide oxidation functions, were differentially expressed between seagrass- and alga-covered sediment locations. In contrast to previous studies, the identification of multiple endosymbiont taxa within and across C. orbiculata individuals, which were also shared with other sympatric lucinid species, suggests that neither host nor endosymbiont displays strict taxonomic specificity. This necessitates further investigations into the nature and extent of specificity of lucinid hosts and their symbionts. IMPORTANCE Symbiont diversity and host/symbiont functions have been comprehensively profiled for only a few lucinid species. In this work, unprecedented thioautotrophic gill endosymbiont taxonomic diversity was characterized within a Ctena orbiculata population associated with both seagrass- and alga-covered sediments. Endosymbiont metabolisms included known chemosynthetic functions and an additional conserved, previously uncharacterized C1 oxidation pathway. Lucinid-symbiont associations were not species specific because this C. orbiculata population hosted multiple endosymbiont strains and species, and other sympatric lucinid species shared overlapping symbiont 16S rRNA gene diversity profiles with C. orbiculata. Our results suggest that lucinid-symbiont association patterns within some host species could be more taxonomically diverse than previously thought. As such, this study highlights the importance of holistic analyses, at the population, community, and even ecosystem levels, in understanding host-microbe association patterns.